Effect of fibre loading on tensile strength of kenaf/glass fibre epoxy hybrid composite for insulator application - Vinoth K.S.; Ansari M.N.M.; Begum S.; Yahya Z.; Atiqah A. (Elsevier Ltd, 2023)
Epoxy composites; Fracture; Fracture mechanics; Glass fibers; Hemp; Hybrid composites; Kenaf fibers; Laminated composites; Reinforcement; Scanning electron microscopy; Epoxy; Fibermat; Glass epoxy; Glass-fibers; Glass/epoxy composite; Hybrid composites; Kenaf/glass fiber hybrid composite; Morphological properties; Vacuum infusion; Vacuum infusion method; Tensile strength